2014
DOI: 10.1371/journal.pone.0086297
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Culture Model of the Developing Small Intestine Offers New Insight in the Early Immunomodulation of Enterocytes and Macrophages by Lactobacillus spp. through STAT1 and NF-kB p65 Translocation

Abstract: The early establishment of a complete microbiome has been shown to play an integral part in the development and maintenance of an intact intestine and its immune system, although much remains unknown about the specific mechanisms of immune modulation in newborns. In our study we show in a co-culture model of the undeveloped small intestine that members of Lactobacillus spp. influence STAT1 and NF-kB p65 nuclear translocation in both intestinal epithelial cells as well as underlying macrophages. Moreover, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Moreover, we found that AGK2 can block the translocation of NFκB stimulated by LPS from the cytosol to the nucleus. Due to the critical roles of nuclear translocation of NFκB in inflammation [42][43][44][45][46], our study has suggested that SIRT2 could mediate neuroinflammation by modulating nuclear translocation of NFκB. These observations, together with our previous finding that SIRT2 silencing can lead to decreased LPS-induced microglial activation-a major event in neuroinflammation [16], have collectively suggested that SIRT2 activity may be required for LPS-induced neuroinflammation.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, we found that AGK2 can block the translocation of NFκB stimulated by LPS from the cytosol to the nucleus. Due to the critical roles of nuclear translocation of NFκB in inflammation [42][43][44][45][46], our study has suggested that SIRT2 could mediate neuroinflammation by modulating nuclear translocation of NFκB. These observations, together with our previous finding that SIRT2 silencing can lead to decreased LPS-induced microglial activation-a major event in neuroinflammation [16], have collectively suggested that SIRT2 activity may be required for LPS-induced neuroinflammation.…”
Section: Discussionsupporting
confidence: 52%
“…L. plantarum strains have been proven to be one of the predominant transient lactobacilli in the jejunum and ileum (54). Besides their Cd sequestration and antioxidative stress activities in the small intestine, L. plantarum strains may interact with dendritic cells in the small intestine lamina propria to influence T cell responses and influence STAT1 and NF-B p65 translocation in the epithelial cells and macrophages of small intestine (55,56). Additionally, a previous human study showed that L. plantarum strains can enhance barrier function by rearrangement of the tight-junction protein conformation in response to Toll-like receptor 2 (TLR2) signaling in the small intestine (52).…”
Section: Discussionmentioning
confidence: 99%
“…21 The infocus single cells were identified by gating on 7-AAD-positive events with high nuclear aspect ratios (minor to major axis ratio, as a measure of circularity) and high nuclear contrast (as measured by the Gradient Max feature). The cells were first stained with the anti-CD45 APC-Cy7 antibody (BD Biosciences, San Jose, CA, USA).…”
Section: Imaging Flow Cytometrymentioning
confidence: 99%